Facile synthesis of TiO2 microspheres via solvothermal alcoholysis method for high performance dye-sensitized solar cells. (1st January 2019) - Mo, Li-E; Li, Zhao-Qian; Ding, You-Cai; Gao, Chun; Hu, Lin-Hua; Huang, Yang; Hayat, Tasawar; Alsaedi, Ahmed; Dai, Song-Yuan
Graphical abstract: Highlights: Facile one-step nonaqueous synthesis strategy to engineer the formation of TiO2 microspheres. The TiO2 microspheres exhibit high specific surface area and large pore size simultaneously. The TiO2 microspheres based DSSC shows high PCE value (10.35%). Abstract: TiO2 microspheres (MS-TiO2 ) are synthesized by a facile one-step nonaqueous solvothermal alcoholysis method. Without any post-processing, the as-prepared MS-TiO2 constituted by high crystallinity anatase nanoparticles (∼18 nm) exhibits large specific surface area (114 m 2 g −1 ), high porosity (71%), and wide pore size distribution (centered at ∼12.4 nm, average pore diameter is ∼20.9 nm). Moreover, the MS-TiO2 shows superior light scattering ability. When employed as photoanode in dye-sensitized solar cells, the MS-TiO2 films display excellent dye loading capacity and good light-harvesting capabilities in the range of 400–700 nm. Consequently, an ultrahigh short circuit current density up to 20.41 mA cm −2 and a high power conversion efficiency of 10.35% are achieved by the MS-TiO2 based solar cells.